مستوى صعوبة القراءة لدى تلامیذ السنة الثالثة ابتدائي من وجهة نظر المعلمین والمعلمات - بن ساسي, حنان (جامعة الوادي - University of Eloued, 2022)
انطلاقا من ما تضمنته الدراسة بجانبيها النظري والميداني يمكن أن القول بان صعوبة القراءة اضطراب شائع بين صفوف السنة الثالثة ابتدائي ويمثل عائق للمعلمين والأهل في سير العملية التعلمية للتلميذ،حيث أن القراءة أساس التعلم، لذلك يجب: -الاهتمام بهذا الموضوع من طرف الطاقم التربوي والأهل. -ضرورة الكشف المبكر من أجل تدارك الأمر. -الاهتمام أكثر بتعليم الهجاء وتخصيص الوقت الكافي لذلك. -يجب الاهتمام باضطرابات اللغة وتأخرها لأن ذلك يؤثر على اكتساب مهارة القراءة. -ضرورة التكفل بذوي صعوبة القراءة في أقسام خاصة على حسب مستوى الصعوبة. -وجود اخصائيين في مجال علم النفس والأرطوفونيا في المدارس من أجل معالجة الاضطرابات والاهتمام أكثر بالتلاميذ. -خلال الدراسة لوحظ وجود قسم كله تقريبا يعاني من صعوبة القراءة وذلك لأن المنطقة نائية وفلاحية(المنشية الشمالية بحاسي خليفة) والأهل يغيبون الأطفال خلال فترات العمل الفلاحي ولا يهتمون بالتعليم، لذلك يجب التنبه لمثل هذه الأخطاء والتعامل مع الأمر بجدية وصرامة من طرف الطاقم التربوي لأن التلاميذ أمانة ويجب المحافظة عليها. Based on what was included in the study in its theoretical and field aspects, it can be said that the difficulty of reading is a common disorder among the third year of primary school and represents an obstacle for teachers and parents in the progress of the student’s learning process, as reading is the basis of learning. Therefore, it must: Attention to this issue on the part of the educational staff and parents. Early detection is necessary in order to remedy the matter. Pay more attention to teaching spelling and allocate enough time for it. Language disorders and delays should be taken care of because this affects the acquisition of reading skill. The need to take care of people with difficulty reading in special sections according to the level of difficulty. The presence of psychologists and orophonia specialists in schools in order to treat disorders and pay more attention to students. -During the study, it was noticed that there is almost an entire section that suffers from difficulty reading, because the area is remote and agricultural (Mansheya North in HassiKhalifa) and the parents miss the children during periods of agricultural work and do not care about education. Pupils are honest and must be preserved.
مذكرة ماستر علم النفس مدرسي
Keywords: صعوبة القراءة، تلاميذ السنة الثالثة; Difficulty reading, third year students